THE ROLE OF LOCAL WISDOM AS RELIGIOUS CONFLICT RESOLUTION IN JAMBI INDONESIA - HM, Pahrudin; Halim, Abdul (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2019)
This research aims at analyzing the potential for social conflict, especially religious conflict related to the establishment of houses of worship in Jambi. This study was conducted by employing a qualitative research approach with a type of case study research. This research was conducted in three districts in Jambi (Telanaipura, Alam Barajo, and Kotabaru). The results show that as a plural city, Jambi is not spared from the conflict of the establishment of places of worship that occurred in three regions. However, the previous conflicts that occurred were not prolonged because the people of Jambi still adhered to the wisdom of the local culture in the form of Seloko Adat which internalized through family, education, and the environment. As a significant potential of a conflict resolution, however, the Jambi society in general are lack of understanding of Seloko Adat.